Praktik Pembelajaran Teks Prosedur Berbasis Proyek di Kelas VII SMP Negeri 4 Cilacap dalam Implementasi Kurikulum Merdeka - Siti Faridah; Eko Suroso (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the practice of project-based procedural text learning in seventh grade at SMP Negeri 4 Cilacap in the context of the implementation of the Independent Curriculum. The approach used was qualitative with a case study method through participatory observation, in-depth interviews, and documentation. The results showed that teachers implemented contextual and project-based learning strategies by utilizing digital media and integrating the values ​​of the Pancasila Student Profile. Students demonstrated active involvement in learning activities, especially in the creation of video tutorials and procedural posters. However, there were still obstacles in the form of teachers' limited understanding of the application of learning differentiation and formative assessment, as well as a lack of adequate digital infrastructure support. This study provides a theoretical contribution to the development of a more contextual and transformative Indonesian language learning model. Practically, these findings can serve as a reference for teachers and policymakers in designing learning strategies relevant to student needs and encouraging the use of innovative media to increase student participation and understanding, particularly in coastal areas.